Mitochondrial Uncoupling Proteins: Subtle Regulators of Cellular Redox Signaling - Ježek, Petr; Holendová, Blanka; Garlid, Keith D; Jabůrek, Martin (Antioxidants & redox signaling, 2018)
SIGNIFICANCE: Mitochondria are the energetic, metabolic, redox, and information signaling centers of the cell. Substrate pressure, mitochondrial network dynamics, and cristae morphology state are integrated by the protonmotive force Δp or its potential component, ΔΨ, which are attenuated by proton backflux into the matrix, termed uncoupling. The mitochondrial uncoupling proteins (UCP1-5) play an eminent role in the regulation of each of the mentioned aspects, being involved in numerous physiological events including redox signaling. Recent Advances: UCP2 structure, including purine nucleotide and fatty acid (FA) binding sites, strongly support the FA cycling mechanism: UCP2 expels FA anions, whereas uncoupling is achieved by the membrane backflux of protonated FA. Nascent FAs, cleaved by phospholipases, are preferential. The resulting Δp dissipation decreases superoxide formation dependent on Δp. UCP-mediated antioxidant protection and its impairment are expected to play a major role in cell physiology and pathology. Moreover, UCP2-mediated aspartate, oxaloacetate, and malate antiport with phosphate is expected to alter metabolism of cancer cells. CRITICAL ISSUES: A wide range of UCP antioxidant effects and participations in redox signaling have been reported; however, mechanisms of UCP activation are still debated. Switching off/on the UCP2 protonophoretic function might serve as redox signaling either by employing/releasing the extra capacity of cell antioxidant systems or by directly increasing/decreasing mitochondrial superoxide sources. Rapid UCP2 degradation, FA levels, elevation of purine nucleotides, decreased Mg2+, or increased pyruvate accumulation may initiate UCP-mediated redox signaling. FUTURE DIRECTIONS: Issues such as UCP2 participation in glucose sensing, neuronal (synaptic) function, and immune cell activation should be elucidated. Antioxid. Redox Signal. 29, 667-714.
Keywords: attenuation of superoxide formation; redox signaling; oxidace-redukce; signální transdukce; antioxidancia; fatty acid cycling; mitochondrial uncoupling proteins; UCP2; Animals; Oxidation-Reduction; lidé; Antioxidants; anion transport; Humans; zvířata; Mitochondrial Uncoupling Proteins; mitochondriální odpřahující proteiny; Signal Transduction